The CCCH zinc finger protein C3H15 negatively regulates cell elongation by inhibiting brassinosteroid signaling. Issue 1 (9th February 2022) - Chai, Guohua; Qi, Guang; Wang, Dian; Zhuang, Yamei; Xu, Hua; Bai, Zetao; Bai, Ming-Yi; Hu, Ruibo; Wang, Zeng-yu; Zhou, Gongke; Kong, Yingzhen
Abstract: Plant CCCH proteins participate in the control of multiple developmental and adaptive processes, but the regulatory mechanisms underlying these processes are not well known. In this study, we showed that the Arabidopsis ( Arabidopsis thaliana ) CCCH protein C3H15 negatively regulates cell elongation by inhibiting brassinosteroid (BR) signaling. Genetic and biochemical evidence showed that C3H15 functions downstream of the receptor BR INSENSITIVE 1 (BRI1) as a negative regulator in the BR pathway. C3H15 is phosphorylated by the GLYCOGEN SYNTHASE KINASE 3 -like kinase BR-INSENSITIVE 2 (BIN2) at Ser111 in the cytoplasm in the absence of BRs. Upon BR perception, C3H15 transcription is enhanced, and the phosphorylation of C3H15 by BIN2 is reduced. The dephosphorylated C3H15 protein accumulates in the nucleus, where C3H15 regulates transcription via G-rich elements (typically GGGAGA). C3H15 and BRASSINAZOLE RESISTANT 1 (BZR1)/BRI1-EMS-SUPPRESSOR 1 (BES1), two central transcriptional regulators of BR signaling, directly suppress each other and share a number of BR-responsive target genes. Moreover, C3H15 antagonizes BZR1 and BES1 to regulate the expression of their shared cell elongation-associated target gene, SMALL AUXIN-UP RNA 15 ( SAUR15 ). This study demonstrates that C3H15-mediated BR signaling may be parallel to, or even attenuate, the dominant BZR1 and BES1 signaling pathways to control cell elongation. This finding expands our understanding of the regulatory mechanisms underlying BR-induced cell elongation in plants. Abstract : The CCCH transcription factor C3H15 antagonizes BZR1 and BES1 to inhibit BR signaling.